Industrial Clusters and Micro and Small Enterprises in Africa : From Survival to Growth - Yoshino, Yutaka (World Bank, 2012)
The private sector is the engine of economic growth, stimulating entrepreneurship and innovation and promoting competition and productivity. While many countries in Africa have developed private sector-driven growth strategies, private investment as a proportion of gross domestic product (GDP) is only 13 percent in Africa, significantly lower than in other regions, such as South Asia, with many low-income countries. The public sector still occupies the lion's share of economic activity in Africa. This study addresses how industrial clusters could be a springboard for the development of Africa's micro and small enterprise sector, which constitutes the bulk of the region's indigenous private sector. The successful development of industrial clusters in Asia illustrates how small enterprises can help to drive growth led by market expansion at home and abroad.